Mono(boratabenzene) rare-earth metal dialkyl complexes: synthesis, structure and catalytic behaviors for styrene polymerization. Issue 12 (25th February 2015) - Wang, Xiufang; Leng, Xuebing; Chen, Yaofeng
Abstract : Synthesis and structural characterization of mono(boratabenzene) rare-earth metal dialkyl complexes were achieved by using multi-substituted boratabenzene ligands, and the synthesized scandium complexes show high catalytic activities for syndiotactic styrene polymerization upon activation with cocatalysts. Abstract : Four mono(boratabenzene) rare-earth metal dialkyl complexes, [(3, 5-Me2 -C5 H3 BR)Ln(CH2 SiMe3 )2 (THF)] (1 : R = NEt2, Ln = Sc;2 : R = NEt2, Ln = Lu;3 : R = Ph, Ln = Sc;4 : R = Ph, Ln = Lu), were synthesized efficiently via a one-pot strategy with Li[ 3, 5-Me2 -C5 H3 BR] (R = NEt2, Ph), LnCl3 (THF) x (Ln = Sc, x = 3; Ln = Lu, x = 0), and LiCH2 SiMe3 . The solid-state structures of1 and2 were determined by single-crystal X-ray diffraction. Variable-temperature NMR studies indicated that the energy barrier for the rotation of aminoboratabenzene in1 (Δ G ‡ ≈ 71 kJ mol −1 ) is higher than that of phenylboratabenzene in3 (Δ G ‡ ≈ 59 kJ mol −1 ). These mono(boratabenzene) rare-earth metal dialkyl complexes' catalytic behaviors for styrene polymerization were investigated, and found that mono(boratabenzene) scandium dialkyl complexes show high catalytic activities for syndiotactic polymerization upon activation with cocatalysts.